2022
DOI: 10.1186/s12967-022-03573-7
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-AC079061.1/VIPR1 axis may suppress the development of hepatocellular carcinoma: a bioinformatics analysis and experimental validation

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most malignant tumors to threaten human life, and the survival rate remains low due to delayed diagnosis. Meanwhile, lncRNAs have great potential for application in tumor prognosis, therefore relevant research in hepatocellular carcinoma is indispensable. Methods Based on the EZH2 expression, the differentially expressed lncRNAs DElncRNAs), miRNAs (DEmiRNAs), and mRNAs (DEmRNAs) were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The 12 characteristic genes are primarily enriched in pathway associated with metabolic process. Among the characteristic gene generated from the model, loss of VIPR1 expression in HCC facilitated CAD phosphorylation and tumor progression, suggesting that the restoration of VIPR1 and treatment with the VIPR1 agonist may represent a promising approach for HCC treatment ( 32 , 36 ). Our research suggested that VIPR1 may play a role in the classification of early stage HCC and advanced HCC, but further research is needed to determine its specific function.…”
Section: Discussionmentioning
confidence: 99%
“…The 12 characteristic genes are primarily enriched in pathway associated with metabolic process. Among the characteristic gene generated from the model, loss of VIPR1 expression in HCC facilitated CAD phosphorylation and tumor progression, suggesting that the restoration of VIPR1 and treatment with the VIPR1 agonist may represent a promising approach for HCC treatment ( 32 , 36 ). Our research suggested that VIPR1 may play a role in the classification of early stage HCC and advanced HCC, but further research is needed to determine its specific function.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ceRNA network, we discovered that Lnc-PCBP1-AS1 plays a pivotal role, which may influence variable targets through 16 lncRNA-associated miRNAs. Interestingly, a number of miRNAs, including miR-363 [40] , miR-125a-5p [41] , miR-193a [42] , miR-4465 [43] , miR-4319 [44] , miR-125b-5p [45] , miR-22-3p [46] , miR-107 [47] , miR-17-5p [48] , miR-20b-5p [49] , and miR-24-3p [50] , have all been associated with the initiation and progression of hepatocellular carcinoma. Furthermore, miR-20b-5p can be sponged by the lncRNA WWOX-AS1, which upregulates WWOX and thereby inhibits the progression of hepatocellular carcinoma [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pseudogene DUXAP8 encouraged HCC cell differentiation by modifying kinase function through DUXAP8/miR-490–5p/BUB1 ( Zhang et al, 2020a ). However, when certain lncRNAs target miRNAs of oncogenes, they often inhibit HCC proliferation, as observed with lncRNA MIR31HG ( Yan et al, 2018 ) and lncRNA-AC079061.1 ( Lin et al, 2022 ).…”
Section: The Role Of Cerna Network In the Development Of Hccmentioning
confidence: 99%